2007
DOI: 10.1016/j.gene.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Rapid fixation of a distinctive sequence motif in the 3′ noncoding region of the clade of West Nile virus invading North America

Abstract: Phylogenetic analysis of complete genomes of West Nile virus (WNV) by a variety of methods supported the hypothesis that North American isolates of WNV constitute a monophyletic group, together with an isolate from Israel and one from Hungary. We used ancestral sequence reconstruction in order to obtain evidence for evolutionary changes that might be correlated with increased virulence in this clade (designated the N.A. clade). There was one amino acid change (I→T at residue 356 of the NS3 protein) that occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In most viral protein-coding genes, the number of synonymous substitutions per synonymous site ( d S ) typically exceeds the number of nonsynonymous substitutions per nonsynonymous site ( d N ), indicating that purifying selection has acted against the latter (Hughes 1999). This pattern has been found in the protein-coding genes of many virus taxa (e.g., Hughes 2007a; Hughes and Hughes 2007; Hughes et al 2007; Hughes and Piontkivska 2008; Irausquin and Hughes 2008). Moreover, in many viruses the rate of nucleotide substitution in non-coding regions is substantially less than d S (though usually not lower than d N ), providing evidence of purifying selection on viral genomes outside protein-coding genes (Hughes 2007a, 2009; Hughes and Piontkivska 2008).…”
Section: Evolutionary Biology Of Viruses: General Considerationsmentioning
confidence: 63%
See 2 more Smart Citations
“…In most viral protein-coding genes, the number of synonymous substitutions per synonymous site ( d S ) typically exceeds the number of nonsynonymous substitutions per nonsynonymous site ( d N ), indicating that purifying selection has acted against the latter (Hughes 1999). This pattern has been found in the protein-coding genes of many virus taxa (e.g., Hughes 2007a; Hughes and Hughes 2007; Hughes et al 2007; Hughes and Piontkivska 2008; Irausquin and Hughes 2008). Moreover, in many viruses the rate of nucleotide substitution in non-coding regions is substantially less than d S (though usually not lower than d N ), providing evidence of purifying selection on viral genomes outside protein-coding genes (Hughes 2007a, 2009; Hughes and Piontkivska 2008).…”
Section: Evolutionary Biology Of Viruses: General Considerationsmentioning
confidence: 63%
“…Evidence of ongoing purifying selection against slightly deleterious nonsynonymous variants is provided by the occurrence of numerous relatively rare nonsynonymous variants (Hughes 2005; Hughes et al 2003); and such a pattern has been seen in many viruses as well as in cellular organisms (Hughes 2007a; Hughes and Hughes 2007; Hughes et al 2007; Hughes and Piontkivska 2008; Irausquin and Hughes 2008). …”
Section: Evolutionary Biology Of Viruses: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent observations showed that nucleotide changes in the 3′-UTR played a role in rapid spread of this virus in the New World because nucleotide changes in the 3′-UTR had co-evolved with amino acid changes and affected interactions of helicase and RNA polymerase with their RNA substrate (33). Mutations in 3′-UTR appear to play a role in production of small-plaque temperature-sensitive variants or mouseattenuated phenotype variants (34).…”
Section: Resultsmentioning
confidence: 99%
“…However, the relevance and role of the identified motifs and associated genome lesions in viral replication and their evolutionary consequences remain to be explored. The relatively high rate of occurrence of mutations, deletions and insertions in the variable region of the 3′UTR suggests that positive Darwinian selection may have acted on this part of the WNV genome [61].…”
Section: Discussionmentioning
confidence: 99%